Cheese characterization and authentication through lipid biomarkers obtained by high-resolution 1H NMR profiling. (30th July 2022) - Haddad, Lenny; Francis, Joseph; Rizk, Toufic; Akoka, Serge; Remaud, Gérald S.; Bejjani, Joseph
Highlights: Cheese authentication using high-resolution 1 H NMR profiling of triacylglycerols. Cheese classification according to the producing species, to the origin and variety. Identification and quantitation of 1 H NMR peaks related to minor fatty acids. Identification of positional fatty acid biomarkers in cheese triacylglycerols. Quantitation of individual fatty acids within cheese triacylglycerols by 1 H NMR. Abstract: Food quality and safety are at the heart of consumers' concerns across the world. Dairy products, because of their large consumption, are fertile ground for fraudulent acts. This fact justifies the development of effective, accessible, and rapid analytical methods for their authentication. A high-resolution spectral treatment method previously developed by our team was applied to 1 H NMR spectra of cheese triacylglycerols. 178 Peaks were thus quantitated and successfully used in the construction of multivariate models for the quantitation of individual fatty acids and for the classification of cheese samples according to the producing species, to their origin and variety. Besides, several peaks related to the amount and position of anteisopentadecanoic, butyric, α-linolenic, myristoleic, rumenic, and vaccenic acids were, among others, specific biomarkers of cheese groups. For the first time in 1 H NMR, we were able to identify and to quantitate signals related to minor fatty acids within cheese triacylglycerols.